Diffuse large B-cell lymphoma of non-germinal center type of the buttock - Tadashi Terada, MD, PhD (Elsevier, 2016)
Primary lymphoma of soft tissue is very rare. An 80-year-old man presented with a right buttock tumor measuring 5 × 5 × 4 cm. Tumorectomy was performed. The tumor was located in the fascia and subcutaneous tissue, and encapsulated by a thin capsule. Histologically, the tumor showed atypical lymphoid cell proliferation. Immunohistochemically, the tumor cells were positive for CD45, CD20, CD79a, and CD138. The Ki-67 labeling was 90%. In contrast, they were negative for pancytokeratins, epithelial membrane antigen, CD10, MUM1, bcl-6, cyclin D1, CD3, CD30, CD45RO, TdT, CD56, S100 protein, HMB45, chromogranin, α-smooth muscle actin, and desmin. A diagnosis of diffuse large B-cell lymphoma (DLBCL) of soft tissue was made. The subtype of DLBCL is non-germinal center type (non-GC). Systemic investigation using various imaging modalities including CT, MRI and Ga-scintigraphy revealed small nodular lesions up to 1 mm in the lungs and liver. However, biopsies of these locations were not performed because of his old age. The nodular lesions of the liver and lungs were small in diameter (up to 1 cm), and it is strongly likely that the buttock tumor is primary. The patient was treated by R-CHOP chemotherapy and radiation. He was referred to another specialized hospital for his will.